Pengaruh Kualitas Produk dan Citra Merek terhadap Keputusan Pembelian pada Roti CV. Rima Bakery di Kota Padang - Maria Magdalena; Suroso Winardi (JURNAL PUNDI, 2020)
CV Rima bakery is a home-based bread company or can be referred to as SMEs (small and medium-sized businesses) that produce bread with a variety of types and flavors that are marketed throughout Padang City, this study aims to determine the effect of product quality, and brand image of consumers on purchasing decisions on bread Cv. Rima Bakery in Padang City. In testing this hypothesis using a t test with a significance level of 5%. Product Moment and Cronbach Alpha of consumer choice are used to measure validity and reliability, tests have been carried out that all variables show valid and reliable. The results of the partial test (t test) that the quality of the product there is a t value of 2.565 with a significant value of 0.11 when compared to t table, t-count is greater than t-table then it can be interpreted or show a significant value of 0.011> 0.05, then Ho is rejected and Ha is accepted and has a positive and significant influence on purchasing decisions, brand image has a t value of 5.813 with a significant value of 0.00 when compared to t table, t-count is greater than t-table, it can be interpreted or show the value significant 0,000 <0.05, then Ho is rejected and Ha is accepted and has a positive and significant influence on purchasing decisions.  Keywords: product quality, brand image, purchasing decisions.